Intrinsic (Trap‐Free) Transistors Based on Epitaxial Single‐Crystal Perovskites. Issue 43 (25th September 2022) - Bruevich, Vladimir; Kasaei, Leila; Rangan, Sylvie; Hijazi, Hussein; Zhang, Zhenyuan; Emge, Thomas; Andrei, Eva Y.; Bartynski, Robert A.; Feldman, Leonard C.; Podzorov, Vitaly
Abstract: The first experimental realization of the intrinsic (not dominated by defects) charge conduction regime in lead‐halide perovskite field‐effect transistors (FETs) is reported. The advance is enabled by: i) a new vapor‐phase epitaxy technique that results in large‐area single‐crystalline cesium lead bromide (CsPbBr3 ) films with excellent structural and surface properties, including atomically flat surface morphology, essentially free from defects and traps at the level relevant to device operation; ii) an extensive materials analysis of these films using a variety of thin‐film and surface probes certifying the chemical and structural quality of the material; and iii) the fabrication of nearly ideal (trap‐free) FETs with characteristics superior to any reported to date. These devices allow the investigation of the intrinsic FET and (gated) Hall‐effect carrier mobilities as functions of temperature. The intrinsic mobility is found to increase on cooling from ≈30 cm 2 V −1 s −1 at room temperature to ≈250 cm 2 V −1 s −1 at 50 K, revealing a band transport limited by phonon scattering. Establishing the intrinsic (phonon‐limited) mobility provides a solid test for theoretical descriptions of carrier transport in perovskites, reveals basic limits to the technology, and points to a path for future high‐performance perovskite electronic devices. Abstract : Intrinsic (trap‐free) field‐effect transistors based on epitaxial single‐crystalline CsPbBr3 perovskite films are reported. Extensive structural, electrical, and gated Hall‐effect characterization confirms outstanding quality of the material and a nearly ideal transistor behavior. Hole mobility of 30 cm 2 V −1 s −1 at room temperature, monotonically increasing on cooling to 250 cm 2 V −1 s −1 at 50 K, is measured in these transistors.